2000
DOI: 10.1038/sj.bjp.0703559
|View full text |Cite
|
Sign up to set email alerts
|

Effect of saikosaponin, a triterpene saponin, on apoptosis in lymphocytes: association with c‐myc, p53, and bcl‐2 mRNA

Abstract: 1 The mechanisms involved in the apoptotic e ect of saikosaponin-d, a triterpene saponin from Bupleurum falcatum L., were studied in human CEM lymphocytes and compared with those of dexamethasone (3610 77 M). 6 Levels of c-myc, p53, and bcl-2 mRNA were analysed by the reverse transcription-polymerase chain reaction. Levels of c-myc and p53 mRNA were signi®cantly increased, while the level of bcl-2 mRNA was decreased, by saikosaponin-d (10 75 M) treatment. Dexamethasone did not signi®cantly change the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 40 publications
2
20
1
Order By: Relevance
“…Saikosaponins (A, B and D), the major components of Bupleuri Radix, have attracted a great deal of attention as anticancer agents [34][35][36][37]. Wu et al [34] reported that the increase of p-15…”
Section: Discussionmentioning
confidence: 99%
“…Saikosaponins (A, B and D), the major components of Bupleuri Radix, have attracted a great deal of attention as anticancer agents [34][35][36][37]. Wu et al [34] reported that the increase of p-15…”
Section: Discussionmentioning
confidence: 99%
“…Triterpenoids exert various pharmacological effects to control many diseases, including cancer [3,6,[33][34][35][36]. The present study is the first to evaluate the potential anti-tumoural effects of maslinic acid, a new triterpenoid isolated as a majority compound from olive-pelt pomace.…”
Section: Discussionmentioning
confidence: 99%
“…So, high cytotoxic potential may be attributed to corchorusins which are abundant in seeds of Corchorus sp. (Khan et al, 2006), having structural similarity with saikosaponins (Hsu et al, 2000;Mahato & Pal, 1987). Saikosaponins and saikosaponin-like compounds have been reported to possess potent antitumor activity (Bachran et al, 2008).…”
Section: Discussionmentioning
confidence: 99%